Effects of 7-week resistance training on handcycle performance in able-bodied males - Abonie, U. S.; Albada, T.; Morrien, F.; van der Woude, L.; Hettinga, F. (International Journal of Sports Medicine, 2022)
The effect of an upper body resistance training program on maximal and submaximal handcycling performance in able-bodied males was explored. Eighteen able-bodied men were randomly assigned to a training group (TG: n=10) and a control group (CG: n=8). TG received 7 weeks of upper body resistance training (60% of 1 repetition maximum (1RM), 3×10 repetitions, 6 exercise stations, 2 times per week). CG received no training. Peak values for oxygen uptake (V?O2peak), power output (POpeak), heart rate (HRpeak), minute ventilation (V?OEpeak) and respiratory exchange ratio (RERpeak), submaximal values (HR, V?O2, RER, PO, and gross mechanical efficiency (GE)), and time to exhaustion (TTE) were determined in an incremental test pre- and post-training. Maximal isokinetic arm strength and 1RM tests were conducted. Ratings of perceived exertion (RPE) were assessed. A two-way repeated measures ANOVA and post-hoc comparisons were performed to examine the effect of time, group and its interaction (p<0.05). TG improved on POpeak (8.55%), TTE (10.73%), and 1RM (12.28-38.98%). RPE at the same stage during pre- and post-test was lower during the post-test (8.17%). Despite no improvements in V?O2peak, training improved POpeak, muscular strength, and TTE. Upper body resistance training has the potential to improve handcycling performance.